A secure method of voting and planning based on quadratic voting - Hamid Devisti; Massoud Hadian Dehkordi (AUT Journal of Mathematics and Computing)
Recently, an innovative voting method named quadratic voting ($QV$) has been proposed which allows people to vote as much as they want, according to their preferences intensity. Little research has been done on the safe implementation of this method. In this paper, we first present a voting method based on $QV$. This method combines the voting and planning, and gives the ability to voters to express their opinions about the candidates programs in addition to voting. Then, a secure electronic voting protocol is proposed for implementing our method. This protocol gives the voters to check the verifiability of ballots and the safety of payment so that they would be sure that their votes are counted correctly.